THE ISLAMIC THEOCRATIC PRACTICE AND THE OTHER IN NIGERIA SINCE DEMOCRATIZATION - Saheed Ahmad Rufai (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This paper’s hypothetical view is that theocracy as a concept is so self-explanatory that little or no special learning is required to discern it. This is based on the fact that almosteveryone has an idea of what government and religion mean and how they function or operate. Connecting religious institutions to government or the reverse is therefore not expected to prove challenging. However, the need for scholarly precision or appreciable level intellectual accuracy informs the need to critically rethink the concepts with regard to the status or place of The Other. Whereas the Islamic theocratic principles and practice in Nigeria are the subject of the paper, non-Muslims, contextually mentioned as The Other. This paper attempts to identify issues revolving around the experience of The Other in an Islamic theocracy, with a focus on Nigeria since its return to democratic rule in 1999. The paper which uses both historical and analytical methods seeks to systematically stimulate further engagement with the Islamic theoretical principles and practices as understood in the country during the period under coverage, in connection with issues and challenges involving the non-Muslims.